2008
DOI: 10.2500/ajr.2008.22.3222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Rhinosinusitis and Endoscopic Sinus Surgery on Bone Remodeling of the Paranasal Sinuses

Abstract: In the revision ESS group, soft tissue and bone remodeling may be greater than in the primary ESS group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Bone remodeling of the paranasal sinuses can be affected by many factors including age, sex, chronic inflammation, and surgery (11). In our study group, obstruction due to NP might be the only causative factor for the obvious remodeling of the maxillary arch.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bone remodeling of the paranasal sinuses can be affected by many factors including age, sex, chronic inflammation, and surgery (11). In our study group, obstruction due to NP might be the only causative factor for the obvious remodeling of the maxillary arch.…”
Section: Discussionmentioning
confidence: 77%
“…NP is known to be associated with bronchial asthma and a number of topical and systemic diseases of different origins (11)(12)(13). The exact origin of NP is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…390,392 Lee et al 392 found an increased incidence of osteitis according to pathologic features in patients with CRS undergoing a revision sinus surgery (58%) compared to those with CRS undergoing primary surgery (6.7%), but did not differentiate between CRSsNP and CRSwNP patients. The estimated prevalence of osteitis in CRS patients based on radiographic criteria or histopathology is 32.5% to 79%, 399,400 which underscores the potential clinical impact of this finding.…”
Section: S55mentioning
confidence: 85%
“…Of note, previous surgery has been associated with worsened osteitis scores in several studies, suggesting osteitis may be a marker of more severe disease and/or possibly a reaction to previous surgery. 386,399,401,402 The causality and relationship of bacterial biofilms, mucosal pathology, and bacterial infection is not well understood in relationship to osteitis. Bacterial infection of the bone is an unlikely cause of osteitis in CRS patients.…”
Section: S55mentioning
confidence: 99%
“…d CRSsNP, fibrotic fields: expression of type IV collagen (type IV collagen staining ×200) rather than purely subsequent to inflammation. But repeated injuries, as revision endoscopic sinus surgery (ESS) group, acting in a cumulative way, induced higher degree of tissue or bone remodeling [15].…”
Section: Real Sequence In Remodeling Features or Preferential Associamentioning
confidence: 99%